Cryptocarbon: The promises and pitfalls of forest protection on a blockchain. Issue 100 (March 2019) - Howson, Peter; Oakes, Sarah; Baynham-Herd, Zachary; Swords, Jon
Highlights: Blockchain technology offers a funding lifeline to existing REDD+ projects. Cryptocarbon creates social and political challenges that have so far escaped critical scrutiny. Smart contracts and AI will shape human relationships with forests over the coming decades. Abstract: In this commentary, we explore how blockchain is being leveraged to address the fundamental problems with market-based forest protection globally. In doing so, we consider the ways 'cryptocarbon' initiatives are creating new challenges that have so far escaped critical scrutiny. A blockchain is a distributed and immutable electronic database – a ledger of every transaction that has ever taken place on a network, stored as cryptographically secured blocks, strung together in a chain. The technology is being increasingly hyped as applicable for a whole range of industries, social service provisions, and environmental management concerns. This includes the facilitation of natural asset market mechanisms, like Reducing Emissions from Deforestation and Forest Degradation (REDD+). The original aim of REDD+ was to incentivise conservation, making tropical forests more valuable standing than cut down. Multiple factors, including lack of consumer interest, created an oversupply of carbon commodities. Ninety-five percent of the world's avoided deforestation credits, representing millions of hectares of conserved forest, were stuck without a buyer. Several flagging REDD+ projects are now hoping that blockchain technology can carry them to new heights of market capitalisation. However, like with any powerful new technology, the benefits remain ambiguous.